Engaging with Spirituality in Family Therapy Meeting in Sacred Space (AFTA SpringerBriefs in Family Therapy,, 2018)
This inspiring volume presents a unique and ethical professional framework for engaging in spiritual discussion in the context of family therapy. Addressing existential contradictions of life that can disrupt family functioning as well as religious restrictions that can create relational barriers, it models an open frame of mind for sensitive and respectful metaphysical work with diverse families. Chapter authors build on their own narratives of spiritual journey as they inform conversation with clients whose faith perspectives include Christianity, Judaism, Islam, African and Native American spiritual practice, Taoism, and Sikhism. These powerful dialogues illuminate the deeper tasks of therapy and offer significant opportunities for all family members to be involved in creating meaning and healing together. This one-of-a-kind book: Presents the narratives of a racially, culturally, and religiously diverse group of authors Explores the challenges of metaphysical psychotherapeutic practice Focuses on the intersection of therapeutic practice and spirituality in various cultural contexts Guides therapists in looking into their own spiritual lives and experience Models methods for therapists using spirituality in sessions with families Challenging professionals to step beyond the perceived boundaries of the therapist/client relationship, Engaging with Spirituality in Family Therapy: Meeting in Sacred Space is rich and eloquent reading for practitioners and researchers in family therapy. .